Analysis of the Influence of Interest Rate Effectiveness, Inflation, and Exchange Rates in Stimulating Economic Growth in Indonesia - Vina Ramadhani Siregar; Bakhtiar Efendi; Rusiadi Rusiadi (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study investigates the impact of interest rate effectiveness, inflation, and exchange rates on economic growth in Indonesia between 2014 and 2023. Using a simultaneous equation model and the Two-Stage Least Squares (TSLS) estimation technique, the research analyzes the interrelationships among key macroeconomic indicators. The results show that exports and investment significantly influence GDP, whereas the exchange rate and money supply have no notable effect. Furthermore, GDP growth is identified as a significant determinant of investment, while interest rates and inflation are found to be statistically insignificant. The diagnostic tests confirm that the regression model satisfies the classical assumptions of normality and absence of autocorrelation. These findings highlight the importance of promoting exports and enhancing investment to support Indonesia’s sustainable economic development. Policymakers are encouraged to focus on trade performance and investment climate, as these factors have a stronger direct impact on growth compared to inflation and interest rates during the observed period.